2018
DOI: 10.1177/1470785318770134
|View full text |Cite
|
Sign up to set email alerts
|

International market-oriented strategies for medical tourism destinations

Abstract: Patients seeking medical care are traveling greater distances for treatment. The globalization of health care has given rise to a thriving global medical services industry. The ability to gain access to more advanced treatments and differences in cost and inflexible national health care systems encourage patients to seek treatment abroad. In the new information age, patients seek information about available treatment opportunities with less regard to national boundaries. International hospitals are seeking new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 40 publications
0
11
0
1
Order By: Relevance
“…China is the biggest outbound tourism market at present and in the coming future [16]. Detailed understanding and research of this market would increase the knowledge of the hospitality industry.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…China is the biggest outbound tourism market at present and in the coming future [16]. Detailed understanding and research of this market would increase the knowledge of the hospitality industry.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, It was claimed that excellent medical facilities and qualified medical staff were key factors to attract medical tourists [15]. It was indicated that enhancing the quality of a product of health tourism would improve tourists' satisfaction [16].…”
Section: Health Tourism Research and Its Developmentmentioning
confidence: 99%
“…The international healthcare system has recently registered an increase in the medical tourism service worldwide [ 4 , 16 ]. Related studies in this field have attempted to understand this phenomenon and investigate individuals’ motivations behind seeking such services overseas [ 4 , 17 , 18 ].…”
Section: Review Of Literature and Hypotheses Developmentmentioning
confidence: 99%
“…summer holiday destinations, winter holiday destinations, etc.) and business tourism can be further classified based on the industry classification (e.g., medical tourism (Borg, Ljungbo, 2018); food tourism (Robinson, Getz, Dolnicar, 2018); shopping tourism (Choi, Law, Heo, 2018); etc.) ( Figure 1).…”
Section: Holistic Tourist Satisfaction Index Model For Lithuaniamentioning
confidence: 99%